Sosialisasi KUHP Nasional (UU No. 1 Tahun 2023) untuk Meningkatkan Kesadaran Hukum Pemuda Negeri Makariki - Jusuf Leiwakabessy; Michael R. Singkery; O. Duparlira; F. Koritelu; S. Tukane; K. Suitela (Institut Nalanda, 2026)
Indonesia is experiencing a transition period in criminal law from the Dutch colonial legacy to the new National Criminal Code (KUHP), namely Law No. 1 of 2023. However, information regarding this legal change has not been fully understood by people in rural areas, especially teenagers and youth. This community service aims to increase the legal understanding and awareness of the youth in Negeri Makariki regarding the theories, prohibitions, and sanctions in the new KUHP. The method used is a qualitative-descriptive approach through interactive counseling entitled Legal Talk, coupled with participatory observation of the participants' enthusiasm and responses. The results show that through the delivery of simple materials, participants can understand the fundamental differences between the old and new laws. The youth of Negeri Makariki understand the concept of restorative justice, the rules of limited complaint offenses in morality articles, and criminal threats against everyday problems such as alcohol, narcotics, and theft. This activity successfully straightened out various legal myths in the community and increased the younger generation's vigilance against criminal acts.